Chloroquine neither eliminates liver stage parasites nor delays their development in a murine Chemoprophylaxis Vaccination model - Sahu, Tejram; Lambert, Lynn; Herrod, Jessica; Conteh, Solomon; Orr-Gonzalez, Sachy; Carter, Dariyen; Duffy, Patrick E. (Frontiers in Microbiology, 2015)
Chemoprophylaxis Vaccination (CVac) confers long lasting sterile protection against homologous parasite strains in humans, and involves inoculation of infectious sporozoites under drug cover. CVac using the drug chloroquine (CQ) induces pre-erythrocytic immunity in humans that includes antibody to sporozoites and T-cell responses to liver stage parasites. The mechanism by which CVac with CQ induces strong protective immunity is not understood as untreated infections do not confer protection. CQ kills blood stage parasites, but its effect on liver stage parasites is poorly studied. Here we hypothesized that CQ may prolong or perturb liver stage development of Plasmodium, as a potential explanation for enhanced pre-erythrocytic immune responses. Balb/c mice with or without CQ prophylaxis were infected with sporozoite forms of a luciferase-expressing rodent parasite, Plasmodium yoelii-Luc (Py-Luc). Mice that received primaquine (PQ), a drug that kills liver stage parasites, served as a positive control of drug effect. Parasite burden in liver was measured both by bioluminescence and by qRT-PCR quantification of parasite transcript. Time to appearance of parasites in the blood was monitored by microscopic analysis of Giemsa-stained thick and thin blood smears. The parasite load in livers of CQ-treated and untreated mice did not significantly differ at any of the time points studied. Parasites appeared in the blood smears of both CQ-treated and untreated mice 3 days after infection. Taken together, our findings confirm that CQ neither eliminates liver stage parasites nor delays their development. Further investigations into the mechanism of CQ-induced protection after CVac are required, and may give insights relevant to drug and vaccine development.